1993
DOI: 10.1177/106591299304600403
|View full text |Cite
|
Sign up to set email alerts
|

Organized Labor in the Electorate, 1960-1988

Abstract: This paper examines the union effect on vote choice and turnout in presidential elections from 1960 to 1988. It shows that union household status had a significant effect on vote choice in the last four presidential elections, including the widely reported debacle of 1984. Declining membership and other political-economic factors may explain organized labor's apparent political weakness, but these explanations have very different implications for our thinking about labor politics than the argument that leaders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…Delaney et al (1988) found that union members were more likely to vote, and that COPE endorsements stimulated member turnout in congressional elections. Juravich and Shergold (1988) found no relationship between the receipt of union literature and union member turnout for the 1984 presidential race, while Sousa (1993) found a union effect on turnout for only two of eight presidential elections between 1960 and 1988.…”
Section: Past Researchmentioning
confidence: 93%
See 1 more Smart Citation
“…Delaney et al (1988) found that union members were more likely to vote, and that COPE endorsements stimulated member turnout in congressional elections. Juravich and Shergold (1988) found no relationship between the receipt of union literature and union member turnout for the 1984 presidential race, while Sousa (1993) found a union effect on turnout for only two of eight presidential elections between 1960 and 1988.…”
Section: Past Researchmentioning
confidence: 93%
“…Since Masters and Delaney's (1987) review, a handful of articles have been published that begin to address the relationship between union outreach strategy and member voting behavior. One consistent finding is that union members are more likely than nonmembers to prefer labor-endorsed candidates (Juravich and Shergold 1988;Delaney et al 1990;Hojnacki and Baum 1992;Sousa 1993). Moreover, this choice is correlated with union outreach and Committee on Political Education (COPE) endorsements (Juravich and Shergold 1988;Delaney et al 1990;Hojnacki and Baum 1992).…”
Section: Past Researchmentioning
confidence: 95%
“…The first focuses on differences between union members and the broader electorate. Research has established a pattern of union bloc voting (Sousa, 1993). In addition, some research has shown a noticeable union-nonunion gap in voter turnout (e.g., Uhlaner, 1989).…”
Section: Union Members' Political Attitudes and Behaviorsmentioning
confidence: 99%
“…Research reveals that unions have had considerable political influence (Sheppard and Masters, 1959;Wolfe, 1969;Sousa, 1993;Greenstone, 1997). However, rank-and-file members are not politically homogeneous (Blume, 1970).…”
mentioning
confidence: 99%
“…In the nine presidential elections since 1960 in which the AFL-CIO and most unions endorsed one candidate, a majority of union members have voted for that candidate every time (Table 1).t In two recent elections, the union-endorsed presidential candidate received 62.6 (1988) and 68.0 (1996) percent of the union member vote (Sousa, 1993;"Union Effort," 1996).…”
mentioning
confidence: 99%